THE EFFECT OF JOB MOTIVATION AND JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE WITH JOB INSECURITY MEDIATION (Case Study on Credit Marketing Officer of PT. Maybank Indonesia Finance) - Chandra Prasetya, Andrian; Desy Purnama, Eka; Wahyoedi, Soegeng (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the effect of work motivation and job satisfaction and organizational commitment on employee performance mediated by job insecurity, this research was conducted at PT. Maybank Indonesia Finance, with the research subject namely Credit Marketing Officer. Total population as many as 233 people, with a sample taken 70 respondents. This study used descriptive and verification methods and data collection techniques used questionnaires and literature studies, as well as for data analysis techniques in this study using SmartPLS-SEM (Partial Least Square-Structural Equation Modeling) software, with the aim of testing and analyzing data. . The results obtained in this study indicate that there is a significant influence on work motivation on performance. That there is no significant effect on job satisfaction on performance. That there is no significant effect on organizational commitment to performance. That there is no significant effect on work motivation on Job Insecurity. That there is a significant influence on job satisfaction on Job Insecurity. That there is a significant influence on organizational commitment to Job Insecurity. That there is no significant effect on Job Insecurity on performance. That Job Insecurity does not mediate work motivation on performance. That Job Insecurity does not mediate job satisfaction on performance. That Job Insecurity does not mediate organizational commitment to performance.